Комбінований вплив вуглецевих нанотрубок і ВВЧ-випромінювання на сперматозоїди чоловіків у нормі і патології - Ivanov, L. V.; Kartel, M. T.; Kramar, M. I.; Kolbun, N. D. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2012)
A comparative study of the weak extremely high-frequency radiation in the presence of carbon nanotubes on the mobility of sperm of healthy men and patients with asthenospermia and oligoastenos-permia is carried out. The effect of radiation in the presence of nanotubes in suspension of sperm from healthy men significantly increases their motile time). The level of the mobile fraction of semen remains within the norms are (over 50%) for 8 h, while in the control level of the mobile fraction pas gives less than 50% already for 4 h. For patients with asthenospermia and oligoastenospermia combined effect of extremely high-frequency radiation and carbon nanotubes maintains sufficient activity of the mobile fraction for 6 h. The study of the protective action of radiation and nanotubes on the sperm subjected to cryopreservation showed that a significant positive effect (almost complete recovery of the initial mobility) is observed only in the case of a combined effect. It is suggested that a major factor in the sharp increase of motile sperm of patients with asthenospermia and oligoastenospermia under the influence of extremely radiation is to increase the synthesis of ATP in the cells, which determines their motility and viability. The role of carbon nanotubes as conductive systems is reduced, apparently, for the accumulation and maintaining of high levels of electromagnetic radiation of this type and acoustoelectric waves on the surface of the membrane, as well as to translate radiation energy inside cells to mitochondria and other intracellular organelles.